2019
DOI: 10.1097/md.0000000000016542
|View full text |Cite
|
Sign up to set email alerts
|

Real-world experience with pembrolizumab in patients with advanced melanoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 45 publications
4
19
3
Order By: Relevance
“…Since 2011, a series of novel immuno-oncology (I-O) agents, targeted therapies, and combination regimens have been approved. 1 Robust data from phase III trials [2][3][4][5][6][7] and subsequent real-world evidence [8][9][10] have unequivocally demonstrated overall survival (OS) and progression-free survival (PFS) benefits with these agents. As the follow-up of pivotal trials continues, a substantial body of long-term data is emerging that supports the durability of survival with some agents.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2011, a series of novel immuno-oncology (I-O) agents, targeted therapies, and combination regimens have been approved. 1 Robust data from phase III trials [2][3][4][5][6][7] and subsequent real-world evidence [8][9][10] have unequivocally demonstrated overall survival (OS) and progression-free survival (PFS) benefits with these agents. As the follow-up of pivotal trials continues, a substantial body of long-term data is emerging that supports the durability of survival with some agents.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies exploring the real-world treatment patterns among all adults for late-stage melanoma reported that only 34% to 37% of the patients received ICI as the first-line treatment, despite the recommendation by the NCCN guidelines. [ 24 26 ] The rates of treatment with ICI in our study is very low (6%). A plausible reason for the low rate can be due to the differences in population studied.…”
Section: Discussionmentioning
confidence: 60%
“…These findings demonstrate the effectiveness of pembrolizumab in the actual clinical setting. 34 Another study found that pembrolizumab was used for intravenous infusion (escalating doses 2 or 10 mg/kg) until disease progression or severe toxicity. During the study, 80% of patients had nausea and fever, and it elevated aspartate aminotransferase/alanine aminotransferase.…”
Section: Anti-pd-1 Prevent Malignant Tumorsmentioning
confidence: 99%